Vegetation Structure and Composition in Core Area of Sariska National Park, Rajasthan - Kidwai, Zaara (Indian Forester, 2013)
Species richness, diversity, basal cover and importance value index of the vegetation was analyzed in the Sariska National Park in the north-eastern part of Rajasthan from February to May 2009. Sixteen transects ranging from 1.8 to 2 km in length were laid throughout the 80 km2 study area covering all the available habitat types. EstimateSWin750, PCORD, and TWINSPAN were used to calculate richness, diversity, and dominance of the region. The observed mean tree density (258.44/ha) was lower than the mean shrub density (1178.74/ha), though the diversity value was found to be higher for trees (46.47Â±0.53) compared to shrubs (8.0Â±0.02). Majority of the intensive study area comprised of grasses (56.74%). Anogeissus pendulawas found to be the most dominant species with GBH of individuals within class interval of mostly 40-50 cm and highest IVI value (44.01). Whereas for Acacia senegal the IVI value came out to be the lowest (8.98).